Brucella orchitis: A case report on a rare cause of scrotal abscess leading to orchiectomy - Behnam Dejman; Fereshteh Rahdan; Majid Dezhman; Dariush Rahdan; Ahmad Movahedpour; Fatemeh Salahpour-Anarjan (Urology Case Reports, 2025)
Brucellosis, a zoonotic infection common in Iran, rarely causes genitourinary complications such as orchitis. We report a 65-year-old Persian cattle farmer with brucellosis who developed a testicular abscess despite antibiotic therapy. Initial treatment with rifampin and doxycycline resolved systemic symptoms, but scrotal pain prompted ultrasound, revealing a right testicular abscess. Orchiectomy was performed due to extensive necrosis, with histopathology confirming necrotizing brucellar orchitis. Post-surgical levofloxacin and clindamycin prevented recurrence at six months. This case highlights the need to consider Brucella orchitis in endemic regions when scrotal pathology persists, as advanced cases may require surgical intervention.